ERROR ANALYSIS IN SOLVING GEOMETRY PROBLEMS BASED ON NEWMAN'S ERROR ANALYSIS REVIEWED FROM LEARNING STYLES - Fetty Nuritasari; Septi Dariyatul Aini (FKIP Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to describe the types of student errors in solving problems based on Newman Error Analysis (NEA) in terms of learning styles, namely visual, auditory, and kinesthetic. This type of research uses qualitative-descriptive research. The technique used to collect data in this study was to fill out a learning style questionnaire, problem solving tests, interviews, and documentation and then triangulated to obtain valid data. The results showed: (1) subjects with visual learning styles made mistakes at the stage of process skills (process skills) and writing answers (encoding). (2) subjects with auditory learning styles make mistakes in the stages of understanding (comprehension), transformating (transformation), processing skills (process skills) and writing answers (encoding). (3) subjects with a kinesthetic learning style make mistakes in the transformation, process skills, and writing answers (encoding) stages.